STRATEGIC FLEXIBILITY AND CORPORATE RESILIENCE OF OIL AND GAS SERVICING FIRMS IN SOUTH SOUTH, NIGERIA (World Bulletin of Management and Law, 2025)
This study examined the relationship between strategic flexibility and corporate resilience in the oil and gas servicing firms in South-South, Nigeria. The oil and gas servicing firms’ ability to endure in business depends on their connectivity of net- work of their internal and external factors. These have not been more successful because of their inability to have high resilience capacity to withstand the competitive nature of the business world. Thus, it becomes imperative to achieve the objective of this research involving the determination of the relationship between strategic flexibility and corporate resilience which will enable them to be envisioned, get ready for and adjust to unexpected eventualities and gain competitive advantage. As a consequence, research questions and hypotheses were advanced. a sample size of three hundred and fifty-nine (359) employees was drawn from the population of 5000 employees. Data was collected with the use of copies of questionnaire which were administered and distributed to respondents. The ‘simple random sampling technique was employed and data was analysed using spearman’s rank order correlation coefficient. Partial correlation was used to examine the relationship between the dimensions of Strategic Flexibility and the measures of Corporate Resilience. The results showed that the dimension of strategic flexibility improved corporate resilience. The study recommends amongst others, that oil and gas servicing firms’ executives should embrace strategic resilient capacity in their decision making in order to enable them adjust quickly to environmental shocks and unexpected eventualities to be competitively advantageous